Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I had a quick question with which I am not sure how to get started. I've done some time complexity stuff that involves big-oh, omega and theta notation but nothing with sums.

Here is the question: $$ f(n) = \sum_{k=1}^n {k^{3}\over2^{k}} $$

Prove that $$ f(n) = \Theta(1) $$

Any tips, advice or answers to similar questions would be appreciated. Thanks.

share|cite|improve this question

Here is a hands-on approach: for every positive $x$, $x\lt2^x$ hence $x\lt4\cdot2^{x/4}$, which implies that $x^3\lt64\cdot2^{3x/4}$. Thus, $f(n)\leqslant64\sum\limits_{k\geqslant1}2^{-k/4}\lt64/(1-2^{-1/4})$, which is finite. Now, the assertion $f(n)=\Theta(1)$ simply means that the sequence $(f(n))_n$ is bounded, hence we are done.

More generally, for every $|r|\lt1$ and every $a$, $\sum\limits_{k\geqslant1}k^ar^k$ converges.

share|cite|improve this answer

First note that it is sufficient to prove that $f(n) \in \mathcal{O}(1)$, since $f(n)$ is trivially in $\mathcal{\Omega}(n)$. Next note that $$\sum_{k=1}^n k^3 x^k < \sum_{k=1}^{\infty} k^3x^k = S(x) \,\,\,\,\,\,\,\,\, \forall x \in (0,1)$$ Hence, if we prove that $S(x) \in \mathcal{O}_x(1)$, we are done, where $\mathcal{O}_x(1)$ indicates that the constant depends on $x$.

Recall that $$\sum_{k=1}^{\infty} x^k = \dfrac{x}{1-x} = \dfrac1{1-x} - 1$$ Differentiating term by term, with $x \in (0,1)$, we get that $$\sum_{k=1}^{\infty} kx^{k-1} = \dfrac1{(x-1)^2} \implies \sum_{k=1}^{\infty} kx^{k} = \dfrac{x}{(x-1)^2} = \dfrac1{x-1} + \dfrac1{(x-1)^2}$$ Again differentiating term by term we get that $$\sum_{k=1}^{\infty} k^2x^{k-1} = -\dfrac1{(x-1)^2} - \dfrac2{(x-1)^3}$$ Hence, $$\sum_{k=1}^{\infty} k^2x^{k} = -\dfrac{x}{(x-1)^2} - \dfrac{2x}{(x-1)^3} = -\dfrac1{x-1} - \dfrac3{(x-1)^2} - \dfrac2{(x-1)^3}$$ Differentiate this again to get that $$\sum_{k=1}^{\infty}k^3 x^{k-1} = \dfrac1{(x-1)^2} + \dfrac6{(x-1)^3} + \dfrac6{(x-1)^4}$$ Hence, $$\sum_{k=1}^{\infty}k^3 x^{k} = \dfrac{x}{(x-1)^2} + \dfrac{6x}{(x-1)^3} + \dfrac{6x}{(x-1)^4} \in \mathcal{O}_x(1) \,\,\,\,\,\, \forall x \in (0,1)$$ Take $x= \dfrac12$ to get what you want.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.